PREVALENSI CEDERA KEPALA PASCA KECELAKAAN LALU LINTAS DI RSUD MEURAXA BANDA ACEH - Teuku Aditya Kemal; Suariatu Laila (Jurnal Sains Riset, 2021)
Background: Head injury is a public health problem as a cause of death, disability, and mental deficits. According to WHO in 2008, traffic accidents became the tenth cause of death in the world, with 1.21 million deaths and according to WHO in 2011, developing countries became the seventh leading cause of death in the world with 940,000 deaths. The results of RISKESDAS in 2013, the national prevalence of head injuries caused by motorcycle accidents was 40.6%. Methods: The research design used is a descriptive method with a cross sectional approach. The population in this study were all head injury patients at the Meuraxa Regional General Hospital in 2016 as many as 242 people. In this study, researchers took a sample of 173 people based on inclusion and exclusion criteria. The dependent variable is head injury, while the independent variable is a traffic accident. Results: The results showed that from 242 head injury patients, 173 patients diagnosed with head injury after a traffic accident. The prevalence of head injuries after traffic accidents at the Meuraxa Hospital is 71%. Conclusion: From the results of the study, 173 people with a diagnosis of head injury after a traffic accident met the criteria as a sample. With 149 men (86%), and 24 women (14%). Characteristics of the dominant age group who suffered head injuries after traffic accidents were the age group 10-19 years as many as 55 people (32%). The number of patients with mild head injury was 129 people (75%), moderate head injury was 33 people (19%), and severe head injury was 11 people (6%).Keywords: Head Injury, Traffic Accident